Psychometric evaluation of the Malay version of Weight Stigma Exposure Inventory (Wesei) among Malaysian young adults - Ying Gan, Wan; Chen, I-Hua; Tung, Serene En Hui; Huang, Ru-Yi; Poon, Wai Chuen; Siaw, Yan-Li; Li, Wenjia; Chen, Jung-Sheng (SAGE Publications, 2025)
The present study translated the Weight Stigma Exposure Inventory (WeSEI), an instrument assessing observed weight stigma, into Malay, and evaluated its psychometric properties among Malaysian young adults. Young adults who were Malaysian university students provided their informed consent electronically and completed an online survey hosted on Google Forms. Data were collected by recruiting participants via emails or WhatsApp between March and August 2024. The mean age of the participants (N = 691; 26.0% males) was 21.3 years (SD = 2.42). The online survey included the Malay version of WeSEI and demographic information (ie, gender, height, and weight). Height and weight were used to calculate body mass index and classified into 2 weight status groups (higher weight or non-higher weight). Psychometric evaluations included confirmatory factor analysis (CFA), internal consistency, multigroup CFA across gender and weight status groups, and known-group validity between higher weight and non-higher weight groups. The CFA results supported the 7-factor structure for the WeSEI. All subscales of the WeSEI and the entire WeSEI had good internal consistency (ω > 0.85). Multigroup CFA results supported measurement invariance across gender (ie, males vs females) and weight status (ie, higher weight vs non-higher weight) groups. Also, known-group validity was supported because significantly higher WeSEI scores were observed among those in the higher weight group compared to those in the non-higher weight group. The WeSEI is a promising psychometric instrument that can assess observed weight stigma among Malaysian young adults.